سورۂ توبہ میں نفاق: منافقین کی نو اقسام اور عصرِ حاضر میں ان کے اخلاقی و سماجی اسباق کا تجزیاتی مطالعہ: Hypocrisy in Surah At-Tawbah: An Analytical Study of the Nine Categories of Hypocrites and Their Contemporary Social and Moral Lessons (Al-Aasar, 2025)
Surah At-Tawbah is among the chapters of the Qur’an that most powerfully exposes one of the most delicate and complex dimensions of human character: hypocrisy. This paper presents a thematic study of nine principal categories of hypocrites identified in Surah At-Tawbah, examining their attitudes toward faith, obedience to God, collective responsibility, sacrifice, and financial conduct. The study argues that the Qur’anic understanding of hypocrisy extends far beyond mere theological deviation; it portrays a multidimensional moral crisis marked by falsehood, selfishness, fear, miserliness, and social fragmentation. Such traits do not remain confined to the individual but gradually undermine the ethical foundations of society. By situating these Qur’anic teachings within a contemporary context, this research further explores how hypocrisy continues to manifest in modern collective life, including educational institutions, religious circles, and social relationships. In doing so, the paper seeks not only to provide historical insight but also to invite self-reflection, collective integrity, and renewed moral awareness.